ANTIOXIDANT ACTIVITY OF INDONESIAN BROWN MARINE ALGAE (Sargassum turbinarioides) - Artemisia, Rahma; Sinurat, Ellya; Setyowati, Erna Prawita; Martien, Ronny; Nugroho, Akhmad Kharis (Universitas Muhammadiyah Magelang, 2025)
Brown marine algae are provided for an excellent source of bioactive compounds especially fucoidan. Fucoidan is primarily composed of L-fucose residues linked by Î±-1,3 and Î±-1,4 glycosidic bonds, with sulfate groups as its main chemical components. One of the biological activities of fucoidan is antioxidant. Antioxidant activities of Indonesian brown marine algae were investigated. The phytochemical screening of the crude extract was conducted to identify various phytochemical constituents, including carbohydrates, flavonoids, phenolic compound, terpenoids, and proteins and amino acid. The antioxidant activity of the brown marine algae Sargassum turbinarioides was evaluated using free radical scavenging through the DPPH assay and a reducing power assay. The antioxidant capacity of the extracted fucoidan was measured against ascorbic acid, revealing that fucoidan from brown marine algae exhibited lower DPPH radical scavenging activity compared to vitamin C. Meanwhile, the reducing power of the extract increased with higher concentrations, demonstrating a dose-dependent effect. These findings suggest that brown marine algae extract has potential for commercialization as a functional food or dietary supplement owing to its significant antioxidative properties.